The species composition of phytoplankton and phytobenthos of investigated areas of Bookpa river - Abukenova, V.S.; Blyalova, Zh.Zh.; Blyalova, M.Zh. (Fundamental and Experimental Biology, 2019)
In the article the information about the effectiveness of biological methods for determining the degree of saprobity of water bodies by the species composition of microscopic representatives of aquatic algal flora is provided. Algae are a very convenient object for bioindicating thestate of aquatic ecosystems, since they make it unnecessary (or often complementary) to use expensive and laborious physicochemical methods for analyzing environmental parameters; reflect and record the speed of changes occurring in the natural environment. Phy-tohydrobionts, which are bioindicators of pollution, due to theinfluence of certain factors may exhibit different degrees of intensity of the response in the form of domination or partial or complete disappearance. In our opinion, there is a direct relationship between the intensity of the algal indicator reactions and the quality of water. One of the most developed biological methods for assessing water quality using indicator species of phytoplankton and phytobenthos was used — saprobiological analysis of the Pantle-Buck modified by Slade-cek. The possibilities of studying the anatomical and morphological organization of the microscopic flora in the educational process are evaluated. Species of hydrobionts were identified; a list of species inhabiting this water course was also compiled. Indicator organisms were identified, the degree of organic contamination of the studied watercourse was determined.